A knock at midnight : a story of hope, justice, and freedom - Barnett, Brittany K. (Crown, 2020)
"An urgent call to free those buried alive by America's legal system, and an inspiring true story about unwavering belief in humanity-from a gifted young lawyer and important new voice in the movement to transform the system. Brittany K. Barnett was only a law student when she came across the case that would change her life forever-that of Sharanda Jones, single mother, business owner, and, like Brittany, Black daughter of the rural South. A victim of America's devastating war on drugs, Sharanda had been torn away from her young daughter and was serving a life sentence without parole-for a first-time drug offense. In Sharanda, Brittany saw haunting echoes of her own life, both as the daughter of a formerly incarcerated mother and as the once-girlfriend of an abusive drug dealer. As she studied this case, a system came into focus: one where widespread racial injustice forms the core of America's addiction to incarceration. Moved by Sharanda's plight, Brittany set to work to gain her freedom. This had never been the plan. Bright and ambitious, Brittany was a successful accountant on her way to a high-powered future in corporate law. But Sharanda's case opened the door to a harrowing journey through the criminal justice system. By day she moved billion-dollar deals, and by night she worked pro bono to free clients in near-hopeless legal battles. Ultimately, her path transformed her understanding of injustice in the courts, of genius languishing behind bars, and the very definition of freedom itself. Brittany's riveting memoir is at once a coming-of-age story and a powerful evocation of what it takes to bring hope and justice to a system built to resist them both"--